Environmental Concern, Green Perceived Benefits, Green Perceived Quality, Green Awareness Of Price, Generation Z and Green Purchase Decisions (Case Study On The Body Shop Bali) - Gusti Ngurah Giri Tohlangkir (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of environmental concern, green perceived benefits, green perceived quality, and green awareness of price on green purchase decisions for The Body Shop products in Bali, as well as the role of Generation Z as a moderating variable. This study uses a quantitative method with a sample of 135-270 respondents selected using purposive sampling techniques. The results show that environmental concern, perceived green benefits, perceived green quality, and green price awareness have a positive and significant influence on green purchase decisions. Generation Z can moderate the relationship between environmental concern and green purchase decisions, but cannot moderate the relationship between perceived green benefits and green purchase decisions, nor between green price awareness and green purchase decisions. This study contributes to the literature on green consumer behavior and green product marketing strategies.